Analisis Performansi H.264 dan H.265 pada Video Streaming dari Segi Quality Of Service - Vico Andrea Budi Harto; Rakhmadhany Primananda; Aswin Suharsono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Human knowledge has grown. Internet become one of the most useful human's invention. Speaking internet in Indonesia, Telkom declarated FUP on Feb 1 2016. Telkom comparing 320 GB bandwidth with 1,200 movie streaming HD-quality. Of course, streaming video is an interesting thing, but the question arises about the latest codecs such as H.265 that can compresed 50% bandwidth better than H.264. This research make experiment between H.264/AVC and H.265/HEVC compression method. Purpose of this research is to get quantity value from each bitrate, framerate, and bandwidth are used. This research uses streaming duration, throughput, and delay as parameter. The result from measure streaming quality with parameter, streaming duration value at streaming live codec H.264 and H.265 are 22.870 sec, 34.039 sec, streaming store are 10.927 sec, 11.789 sec. Throughput value streaming live codec H.264 dan H.265 are 0.28 Mbit/sec, 0.18 Mbit/sec, streaming store are 0.81 Mbit/sec, 0.79 Mbit/sec. Delay value streaming live codec H.264 and H.265 are 18.04 ms, 24.67 ms, streaming store are 8.47 ms, 8.60 ms. The conclution is streaming H.264 performa is better than H.265, because lower streaming duration, lower delay, and better throughput.